Interference of cinema techniques in Sa'di Yusuf poetry - Burhan, Al-Muqdadi Dalal Ahmed (2020)
Interference of Cinema Techniques in Sa’di Yusuf's poem is one of the new, contemporary, and unexplored topics that were not paid enough attention in research and analysis. Researching such topics will highlight the impact of the new technologies, such as the cinema, on developing the poetic language production. This study attempts to fill this gap in the literature by revealing the role of the cinematic techniques in developing the poetic language. This study aims at describing the cinematic interference as perceived by Sa’di Yusuf in terms of dialectic, animated and whole image. The study serves to define the visual shot in terms of zoom technique for the cinematic camera of the short, middle and general distant shot adopted by Sa’di Yusuf. Furthermore, it analyses Sa’di’s view on the poetic scene (dramatic and mechanical) in terms of its interfering nature and how he has leveraged on the cinematic scene. To this end, an analytical descriptive method was used to analyse the poems in terms of the employment of the cinematic techniques. To do this analysis, the poet’s collection of poetry ‘Three Rivers’ was analysed based on the methodology of "Yousef Al-Sayegh" in terms of the use of cinematographic technique in the contemporary poem. The ways of interference between the poetic art and cinematic art were also analysed. The findings showed that the utilisation of the cinematic image technique has made his poetic language more developed and open. Hence, the employment of the snapshot technique exempted the poet from the linguistic imbalance. Besides, the scenery snapshot technique was able to unite any contradictions in the communicated ideas and display scenery aspects of beauty.